Strengthening the Blue Economy Based on the Utilization of Shell Waste in the Kalibaru Coastal Area - Hakim Hakim; Rismawandi Rismawandi; Desy Mariyani; Lia Diani; Ahmad Zaki Ridhwan (Poltanesa, 2026)
Improving the welfare of coastal communities in Kalibaru, North Jakarta, can be achieved in an integrated manner through circular economy-based management of shellfish waste. This community service activity aims to empower coastal residents by establishing and developing a business that processes shellfish waste into value-added products, specifically paving blocks. The implementation method uses a participatory approach that includes lectures, technical training, and ongoing mentoring in the production process and business management. Participants are encouraged to increase creativity and innovation in product diversification, such as paving blocks, concrete blocks, handicrafts, and squat toilets. The results of the activity show that the community is able to independently process shellfish waste into paving blocks as an effort to manage waste and increase income. Mentoring by a team of lecturers and students plays a crucial role in ensuring the sustainability of the program after the activity. This program has the potential to open new business opportunities and strengthen the economy of the Kalibaru coastal community in a sustainable manner.